Contractor’s entitlement to the costs of acceleration - Masadeh, Aymen (2024)
Contractor’s entitlement to acceleration costs of works remains a controversial issue in the construction globe. This may depend on three essential criteria namely, contract provisions, country legal jurisdiction, and acceleration types: direct, voluntary, or constructive. Therefore, this paper analyses acceleration costs under these criteria and explore courts views around the world and in particular the United Arab Emirates (UAE), and FIDIC Red books (1999 and 1987). This study applies the quantitative and documents analysis methods using primary and secondary resources and the market survey results conducted in the UAE construction industry. The paper concludes construction contracts need to specify express and precise wordings to determine who will bear the acceleration cost. This paper will be the first of its kind to discuss this controversial issue of acceleration costs with a particular focus on UAE using rare and empirical approach.